Classroom techniques : - Allen, Edward David (Harcourt Brace Jovanovich, 1977)
The success of a second-language course depends not only on the quality of the basic program but also on the flexibility with which the teacher uses that program. The aim of this handbook is to show teachers ways of implementing and supplementing existing materials. The suggested teaching procedures may be used with large classes, small groups, and individual students. They may also be used with any method, inasmuch as a special effort has been made to include a variety of teaching approaches. Classroom Techniques contains several outstanding features. First, the reader will note the inclusion of special techniques for teachers of ESL. The emphasis is on elementary and intermediate language classes, although some of the tech- niques are applicable for advanced students. Second, all sample items from foreign languages are accompanied by English equivalents, so that readers can understand them more readily. Third, a wide variety of communication activi- ties has been included for all four language skills. Finally, the chapter on teaching culture reflects recent trends.